2017
DOI: 10.1002/jsfa.8431
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical and functional properties of chum salmon (Oncorhynchus keta) skin gelatin extracted at different temperatures

Abstract: Extracting temperature greatly affected yield, molecular composition and functionalities of GCSS. A temperature lower than 50°C is recommended for GCSS extraction. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…This result was in accordance with the study on gelatine from Wami tilapia, clown featherback and chum salmon where lower gel strength was reported when gelatine was extracted at a higher temperature. 6,8,13 G45 had a higher gel strength compared to commercial bovine gelatine whereas the gel strength of G55 had no significant different with bovine gelatine ( p < 0.05). On the other, the gel strength of G65 and G75 were lower than bovine gelatine ( p < 0.05).…”
Section: Gel Strengthmentioning
confidence: 83%
See 4 more Smart Citations
“…This result was in accordance with the study on gelatine from Wami tilapia, clown featherback and chum salmon where lower gel strength was reported when gelatine was extracted at a higher temperature. 6,8,13 G45 had a higher gel strength compared to commercial bovine gelatine whereas the gel strength of G55 had no significant different with bovine gelatine ( p < 0.05). On the other, the gel strength of G65 and G75 were lower than bovine gelatine ( p < 0.05).…”
Section: Gel Strengthmentioning
confidence: 83%
“…This result suggested that an increase in the random coil of gelatine due to the enhanced hydrolysis of interchain cross-links of collagen which led to the loss of triple helical structure. 6,8 In the amide II region, the absorption bands were found at 1545.11 cm -1 , 1543.78 cm -1 , 1542.10 cm -1 and 1542.69 cm -1 for G45, G55, G65 and G75, respectively. The amide II was contributed by an out-of-phase combination of a CN stretch and in-plane NH deformation modes of the peptide group.…”
Section: Ftir Spectra Of Gelatinementioning
confidence: 98%
See 3 more Smart Citations